Interactions between climate warming and management actions determining bird community change in protected areas - Leonie Jonas; Jon E. Brommer; Martin Jung; Michal Baláž; John J. Borg; Luka Božič; Preben Clausen; Antoine Derouaux; Koen Devos; Cristian Domșa; Sándor Faragó; Niamh Fitzgerald; et al. (Biological Conservation, 2025)

Variation in Biomass Yield and Cell Wall Composition in Switchgrass Natural Variants Under Two Nitrogen Regimes - Mitra Mazarei; Anne E. Harman-Ware; Thomas H. Pendergast; Vivek Shrestha; Yaping Xu; Cristiano Piasecki; Reginald J. Millwood; Katrien M. Devos; C. Neal Stewart (BioEnergy Research, 2025)

Comparative genomic analyses of aerobic planctomycetes isolated from the deep sea and the ocean surface - Lise Øvreås; Nicolai Kallscheuer; Rita Calisto; Nicola Bordin; Julia E. Storesund; Christian Jogler; Damien Devos; Olga Lage (Antonie van Leeuwenhoek, 2025)
On the deep and dark seafloor, a cryptic and yet untapped microbial diversity flourishes around hydrothermal vent systems. This remote environment of difficult accessibility exhibits extreme conditions, including high pressure, steep temperature- and redox gradients, limited availability of oxygen and complete darkness. In this study, we analysed the genomes of three aerobic strains belonging to the phylum Planctomycetota that were isolated from two deep-sea iron- rich hydroxide deposits with low temperature diffusive vents. The vents are located in the Arctic and Pacific Ocean at a depth of 600 and 1,734 m below sea level, respectively. The isolated strains Pr1d T , K2D and TBK1r were analyzed with a focus on genome-encoded features that allow phenotypical adaptations to the low temperature iron-rich deep-sea environment. The comparison with genomes of closely related surface-inhabiting counterparts indicates that the deep-sea isolates do not differ significantly from members of the phylum Planctomycetota inhabiting other habitats, such as macroalgae biofilms and the ocean surface waters. Despite inhabiting extreme environments, our “deep and dark”-strains revealed a mostly non-extreme genome biology.

S01-04 Advancing mixture risk assessment from a regulatory point of view - B. Dujardin; C. Cascio; A. Cafaro; Y. Devos; J.-L.C.M. Dorne; J. Fabrega; G. Giner Santonja; C. Heppner; S. Levorato; L. Mohimont; A. Papanikolaou; E. Solazzo (Toxicology Letters, 2024)

Fecal biomarkers in Italian anthropogenic soil horizons and deposits from Middle Ages and bronze age - M. Bortolini; C. Nicosia; E. Argiriadis; G. Pojana; Y. Devos; D. Battistel (Quaternary Science Reviews, 2024)

Evidence of recent sea-level rise and the formation of a classic Maya canal system inferred from Boca Paila cave sediments, Sian Ka'an biosphere, Mexico - Riley E. Steele; Eduard G. Reinhardt; Frederic Devos; Samuel Meacham; Chris LeMaillot; Jeremy J. Gabriel; Dominique Rissolo; Cesar Arturo Vera; Matthew C. Peros; Sang-Tae Kim; Matthew Marshall; Juliet Zhu (Quaternary Science Reviews, 2023)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Protected area characteristics that help waterbirds respond to climate warming - Elie Gaget; Alison Johnston; Diego Pavón‐Jordán; Aleksi S. Lehikoinen; Brett K. Sandercock; Alaaeldin Soultan; Luka Božič; Preben Clausen; Koen Devos; Cristi Domsa; Vitor Encarnação; Sándor Faragó; et al. (Conservation Biology, 2022)
Protected area networks help species respond to climate warming. However, the contribution of a site's environmental and conservation‐relevant characteristics to these responses is not well understood. We investigated how composition of nonbreeding waterbird communities (97 species) in the European Union Natura 2000 (N2K) network (3018 sites) changed in response to increases in temperature over 25 years in 26 European countries. We measured community reshuffling based on abundance time series collected under the International Waterbird Census relative to N2K sites’ conservation targets, funding, designation period, and management plan status. Waterbird community composition in sites explicitly designated to protect them and with management plans changed more quickly in response to climate warming than in other N2K sites. Temporal community changes were not affected by the designation period despite greater exposure to temperature increase inside late‐designated N2K sites. Sites funded under the LIFE program had lower climate‐driven community changes than sites that did not received LIFE funding. Our findings imply that efficient conservation policy that helps waterbird communities respond to climate warming is associated with sites specifically managed for waterbirds.

Benefits of protected areas for nonbreeding waterbirds adjusting their distributions under climate warming - Elie Gaget; Diego Pavón‐Jordán; Alison Johnston; Aleksi Lehikoinen; Wesley M. Hochachka; Brett K. Sandercock; Alaaeldin Soultan; Hichem Azafzaf; Nadjiba Bendjedda; Taulant Bino; Luka Božič; Preben Clausen; et al. (Conservation Biology, 2021)
Climate warming is driving changes in species distributions and community composition. Many species have a so‐called climatic debt, that is, shifts in range lag behind shifts in temperature isoclines. Inside protected areas (PAs), community changes in response to climate warming can be facilitated by greater colonization rates by warm‐dwelling species, but also mitigated by lowering extirpation rates of cold‐dwelling species. An evaluation of the relative importance of colonization‐extirpation processes is important to inform conservation strategies that aim for both climate debt reduction and species conservation. We assessed the colonization‐extirpation dynamics involved in community changes in response to climate inside and outside PAs. To do so, we used 25 years of occurrence data of nonbreeding waterbirds in the western Palearctic (97 species, 7071 sites, 39 countries, 1993–2017). We used a community temperature index (CTI) framework based on species thermal affinities to investigate species turnover induced by temperature increase. We determined whether thermal community adjustment was associated with colonization by warm‐dwelling species or extirpation of cold‐dwelling species by modeling change in standard deviation of the CTI (CTI SD ). Using linear mixed‐effects models, we investigated whether communities in PAs had lower climatic debt and different patterns of community change than communities outside PAs. For CTI and CTI SD combined, communities inside PAs had more species, higher colonization, lower extirpation, and lower climatic debt (16%) than communities outside PAs. Thus, our results suggest that PAs facilitate 2 independent processes that shape community dynamics and maintain biodiversity. The community adjustment was, however, not sufficiently fast to keep pace with the large temperature increases in the central and northeastern western Palearctic. Our results underline the potential of combining CTI and CTI SD metrics to improve understanding of the colonization‐extirpation patterns driven by climate warming.

Natural Variation in Lignin and Pectin Biosynthesis-Related Genes in Switchgrass (Panicum virgatum L.) and Association of SNP Variants with Dry Matter Traits - Bochra A. Bahri; Guillaume Daverdin; Xiangyang Xu; Jan-Fang Cheng; Kerrie W. Barry; E. Charles Brummer; Ali Missaoui; Katrien M. Devos (BioEnergy Research, 2020)

Reassessment of the evolution of wheat chromosomes 4A, 5A, and 7B - Jan Dvorak; Le Wang; Tingting Zhu; Chad M. Jorgensen; Ming-Cheng Luo; Karin R. Deal; Yong Q. Gu; Bikram S. Gill; Assaf Distelfeld; Katrien M. Devos; Peng Qi; Patrick E. McGuire (Theoretical and Applied Genetics, 2018)

Cell Wall Composition and Underlying QTL in an F1 Pseudo-Testcross Population of Switchgrass - Desalegn D. Serba; Robert W. Sykes; Erica L. Gjersing; Stephen R. Decker; Guillaume Daverdin; Katrien M. Devos; E. Charles Brummer; Malay C. Saha (BioEnergy Research, 2016)

Quantitative Trait Loci (QTL) Underlying Biomass Yield and Plant Height in Switchgrass - Desalegn D. Serba; Guillaume Daverdin; Joseph H. Bouton; Katrien M. Devos; E. Charles Brummer; Malay C. Saha (BioEnergy Research, 2015)

Erratum to: Quantitative Trait Loci (QTL) Underlying Biomass Yield and Plant Height in Switchgrass - Desalegn D. Serba; Guillaume Daverdin; Joseph H. Bouton; Katrien M. Devos; E. Charles Brummer; Malay C. Saha (BioEnergy Research, 2014)

Linkage Maps of Lowland and Upland Tetraploid Switchgrass Ecotypes - Desalegn Serba; Limin Wu; Guillaume Daverdin; Bochra A. Bahri; Xuewen Wang; Andrzej Kilian; Joseph H. Bouton; E. Charles Brummer; Malay C. Saha; Katrien M. Devos (BioEnergy Research, 2013)

Resistance evolution to the first generation of genetically modified Diabrotica-active Bt-maize events by western corn rootworm: management and monitoring considerations - Yann Devos; Lisa N. Meihls; József Kiss; Bruce E. Hibbard (Transgenic Research, 2013)

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

Slowly progressive spinocerebellar ataxia with extrapyramidal signs and mild cognitive impairment (SCA21) - J. Delplanque; D. Devos; I. Vuillaume; A. De Becdelievre; E. Vangelder; C. A. Maurage; K. Dujardin; A. Destée; B. Sablonnière (The Cerebellum, 2008)

Fine mapping of the Pc locus of Sorghum bicolor, a gene controlling the reaction to a fungal pathogen and its host-selective toxin - Ervin D. Nagy; Tso-Ching Lee; Wusirika Ramakrishna; Zijun Xu; Patricia E. Klein; Phillip SanMiguel; Chiu-Ping Cheng; Jingling Li; Katrien M. Devos; Keith Schertz; Larry Dunkle; Jeffrey L. Bennetzen (Theoretical and Applied Genetics, 2007)

An integrated genetic map and a new set of simple sequence repeat markers for pearl millet, Pennisetum glaucum - X. Qi; T. S. Pittaway; S. Lindup; H. Liu; E. Waterman; F. K. Padi; C. T. Hash; J. Zhu; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2004)

Comparative analysis of QTLs affecting domestication traits between two domesticated × wild pearl millet (Pennisetum glaucum L., Poaceae) crosses - V. Poncet; E. Martel; S. Allouis; K. Devos; F. Lamy; A. Sarr; T. Robert (Theoretical and Applied Genetics, 2002)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Habitat use and activity patterns of urban-dwelling javelina - Cindy L. Ticer; Richard A. Ockenfels; James C. Devos; Thomas E. Morrell (Urban Ecosystems, 1998)

Effect of cadmium on the cytoskeleton and morphology of gill chloride cells in parr and smolt Atlantic salmon (Salmo salar) - E. Devos; P. Devos; M. Cornet (Fish Physiology and Biochemistry, 1998)